Voltage security boundary-constrained optimal power flow - Gutiérrez Martínez, Víctor Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
This work presents a new approach to model stability and security constraints in Optimal Power Flow (OPF) problems based on an Artificial Neural Network (ANN) representation of the system security boundary (SB). The novelty of this proposal is that a closed form, differentiable function derived from the system SB is used to represent security constraints in an OPF model. The procedure involves two main steps: First, an ANN representation of the SB is obtained based on Back-Propagation Neural Network (BPNN) training. Second, a differentiable mapping function extracted from the BPNN is used to directly incorporate this function as a constraint in the OPF model. This approach ensures that the operating points resulting from the OPF solution process are within a feasible and secure region, whose limits are better represented using the proposed technique compared to typical security-constrained OPF models. When an insecure operative scenario is identified, the proposed approach uses as a corrective action load shedding, taking advantage of properly knowing the shape of the SB; yielding to determine in an optimal fashion the total amount of load to be curtailed, in such a way that the system returns to the feasible and secure region, taking into account the inherent cost of the load shedding. The effectiveness and feasibility of the proposed approach is demonstrated through the implementation as well as the testing and comparison using the IEEE 2-area and 118-bus benchmark systems of an optimal dispatch technique that guarantees system security in the context of competitive electricity markets.

Este trabajo presenta un nuevo enfoque a la estabilidad del modelo y las restricciones de seguridad en Optimal Power Flow (OPF) problemas basados en una red neuronal artificial (ANN) representación de la seguridad del sistema frontera (SB). La novedad de esta propuesta es que una forma cerrada, función diferenciable derivada del sistema SB se utiliza para representar las restricciones de seguridad en un modelo OPF. El procedimiento involucra dos pasos principales: Primero, se obtiene una representación ANN del SB basada en la formación de la Red Neural de Back-Propagation (BPNN). En segundo lugar, una función de mapeo diferenciable extraída del BPNN se utiliza para incorporar directamente esta función como una restricción en el modelo OPF. Este enfoque asegura que los puntos de operación resultantes del proceso de solución OPF se encuentren dentro de una región factible y segura, cuyos límites se representan mejor usando la técnica propuesta en comparación con los típicos modelos OPF con restricciones de seguridad. Cuando se identifica un escenario operativo inseguro, el enfoque propuesto se utiliza como un desprendimiento de carga de acción correctiva, aprovechando el conocimiento adecuado de la forma del SB; Produciéndose para determinar de una manera óptima la cantidad total de carga que debe ser reducida, de tal manera que el sistema vuelva a la región factible y segura, teniendo en cuenta el coste inherente del desprendimiento de carga. La eficacia y viabilidad del enfoque propuesto se demuestra a través de la implementación, así como la prueba y comparación utilizando los sistemas IEEE de área 2 y 118 bus de una técnica óptima de expedición que garantiza la seguridad del sistema en el contexto de mercados competitivos de electricidad.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: info:eu-repo/classification/cti/7; FIE-D-2011-0023; Voltaje; Seguridad; Flujo de energía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3340